1999
DOI: 10.1159/000014156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increased Brain GABA Concentrations on Breathing in Unanesthetized Newborn Rabbits

Abstract: Evidence suggests that γ-aminobutyric acid (GABA) is involved in control of breathing and in the hypoxia-related ventilatory depression in newborns. However, this evidence is obtained mainly from studies on anesthetized animals. Because anesthesia may interfere with the GABA system, the objectives of our study were to examine effects of GABA on ventilation (VE) and ventilatory response to hypoxia and to reveal effects of repeated hypoxia on GABA concentrations in unanesthetized newborns. The study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This administration method may supress not only the medulla oblongata but also higher brainstem and other brain regions. It was reported that supramedullary brain regions are involved in hypoxic ventilatory depression (Monin et al 1999) and send inhibitory signals to the medulla oblongata during hypoxic exposure due to release and local accumulation of inhibitory neurotransmitters (GABA, dopamine, adenosine). Under these conditions, injection of GABA into the lateral ventricle may suppress hypoxia-induced ventilatory inhibitory mechanisms of the midbrain and pons; this suppression may reverse hypoxic ventilatory depression and even increase ventilation during hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This administration method may supress not only the medulla oblongata but also higher brainstem and other brain regions. It was reported that supramedullary brain regions are involved in hypoxic ventilatory depression (Monin et al 1999) and send inhibitory signals to the medulla oblongata during hypoxic exposure due to release and local accumulation of inhibitory neurotransmitters (GABA, dopamine, adenosine). Under these conditions, injection of GABA into the lateral ventricle may suppress hypoxia-induced ventilatory inhibitory mechanisms of the midbrain and pons; this suppression may reverse hypoxic ventilatory depression and even increase ventilation during hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…3). Therefore, the increased ventilation following exogenous ICV GABA administration may be attributed either to GABA-evoked block of the cerebellar inhibitory input during hypoxia (Monin et al 1999) or to the releasing of the glutamate by the effect of both exogenous GABA and hypoxia, independent of the stimulation of peripheral chemoreceptor afferents. On the other hand, the response of BP was found to be significantly decreased, as expected.…”
Section: Discussionmentioning
confidence: 99%
“…The following pharmaceutics agents can be classified in this group: (1) beta-adrenomimetics [82][83][84]; (2) gutiminebased [82] and (3) GABA-and taurin-based agents [85][86][87][88][89][90], L-carnitine [91].…”
Section: Paas That Decrease Cellular Metabolismmentioning
confidence: 99%
“…Cerebellar outflow processes, consisting of GABAergic neurons, affect a range of somatomotor, autonomic motor (Lutherer et al, 1983; Zhu et al, 2006) and cognitive functions (Schmahmann et al, 2007; Tavano et al, 2007), and serve chemosensing (Xu and Frazier, 1997) and coordination of breathing (Monin et al, 1999) roles. Extensive evidence indicates that adult cerebellar neurons, including Purkinje cells, are predominantly GABAergic (Takayama, 2005) and are inhibitory in function.…”
Section: Introductionmentioning
confidence: 99%